2016
DOI: 10.1002/jms.3736
|View full text |Cite
|
Sign up to set email alerts
|

Low C24‐OH and C22‐OH sulfatides in human renal cell carcinoma

Abstract: . Low C24-OH and C22-OH sulfatides in human renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…In our previous work, we compared 157 tumor and autologous nonmalignant tissues from 80 patients with RCC 18 , and we reported decreased concentrations of monohexosyl sulfatides (SHexCer) with additional hydroxyl in the ceramide part in the tumor tissue compared to the non-neoplastic autologous tissue. These observations are consistent with the results reported by Kim et al 13 . We also found elevated levels of sulfatides composed of two hexosyl units (SHex2Cer) in tumor tissues compared to adjacent nonneoplastic tissues.…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our previous work, we compared 157 tumor and autologous nonmalignant tissues from 80 patients with RCC 18 , and we reported decreased concentrations of monohexosyl sulfatides (SHexCer) with additional hydroxyl in the ceramide part in the tumor tissue compared to the non-neoplastic autologous tissue. These observations are consistent with the results reported by Kim et al 13 . We also found elevated levels of sulfatides composed of two hexosyl units (SHex2Cer) in tumor tissues compared to adjacent nonneoplastic tissues.…”
Section: Introductionsupporting
confidence: 94%
“…Sulfatides, a class of low-abundant sphingolipids, also seem to be a good target for such research 12 . The importance of sulfatide metabolism and sulfotransferase genes expression for the morphological differentiation of tumor and metastatic potentials of the colorectal, ovarian, or renal carcinoma was shown in numerous reports 13,14,15,16,17 . Sulfatides participate in the adhesion to functional proteins, the maintenance and modification of ion channels, and the induction of cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bruker Daltonics). Mass calibration was performed with external standards using lipid-mixed calibration standards with m/z ranges of 674-834 Da (positive ion mode) and 564-906 Da (negative ion mode) prior to data acquisition to achieve a mass accuracy of better than 50 ppm ( 12,24 ). A mass resolution of M/ ⌬ M ‫ف‬ 20,000 was typically achieved in the mass window of PLs.…”
Section: Ims Analysismentioning
confidence: 99%
“…Shotgun lipidomics based on electrospray ionization mass spectrometry (ESI-MS) allows deep molecular profiling of a sample without significant losses of chemical information [26,27]. The high diagnostic potential of lipidomics has been shown in many areas of medicine, particularly in oncology: lung, thyroid gland, breast, stomach, pancreas, colorectal, liver, kidney, prostate, ovarian, and endometrium cancer [28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][51][31][32][33][34][35][36][37]. MS studies of lipid profiles in tissues and blood plasma have revealed new promising biomarkers of endometriosis (benign gynecological disorder) [26,27,32,33,37,44,47].…”
Section: Introductionmentioning
confidence: 99%